Hannah Redmon: capstone - Redmon, Hannah, artist (Colorado State University. Libraries, 2026)
The artist's statement: Fear: noun. 1) the emotion experienced in the presence or threat of danger; 2) an uneasy state of mind usually over the possibility of an anticipated misfortune or trouble. When a mountain lion steps into your path, teeth bared and claws extended, your body reacts accordingly flooding you with enough adrenaline to keep you running or fighting for longer than you normally would be able to. But sometimes there is no mountain lion. Sometimes a mere glance can be enough. With this project, I asked myself what fear and anxiety look like. We know how fear presents itself–the shaking hands, racing heart, and shallow breaths that accompany adrenaline or the freezing of limbs when you realize you can’t run or fight–but fear goes deeper than that. It comes before the physical sensations. What I investigated in this work was what the feeling of fear looks like, and mirrors combined with handwritten text allowed me to do just this. Mirrors and handwriting bridge gaps between our subconscious thoughts and feelings to the outside and literal world. They provide us with a new way of seeing the world around us. By standing in front of a mirror, we are able to physically see the feeling of being human; the way our shirt sits on our skin, the way our hair protrudes from our head, the way our body moves. Through handwriting, we are able to physically see the intangible thoughts inside our minds; the way the lines get more erratic with anxiety, the way the ink smudges from tear drops, the way the pressure changes with anger. The broken glass shards covered with text mimic the sharp, and at times painful, experience of fear that slices away at our minds. The phrases we sometimes tell ourselves like, "Everyone knows," "I'm broken," or "I can't do this" can cause more harm than the broken glass they're placed on if we let them. However, they also show us something vital to this project: fear blinds. When we let our fears take control, life becomes warped and clouded. The positive and beautiful things that surround us everyday, no matter how small they may be, are swallowed up by the darkness. This body of work aims to shift this perspective. When you step up to these mirrors and place yourself in these compositions–your head dipping below the raging waves or your eyes connecting with the gazes of others–something changes. Suddenly, this crippling feeling becomes nothing more than words on a canvas. Suddenly, these fears of judgment or failure are reduced to simple words and not the life-threatening mountain lion we first believed them to be. This work is not complete without you, my viewer. I urge you to step forward. Put yourself in the frame. While you do, I want to ask you something personal, something that will make you think, and hopefully something that will make you realize: What is your fear making you blind to?
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making